Potentials of selected malaysian biomasses as co-gasification fuels with oil palm fronds in a fixed-bed downdraft gasifier - Moni, M.N.Z. (EDP Sciences, 2014)
Oil palm frond (OPF) has been successfully gasified to produce syngas and has since deemed as a potential source of biomass fuel in Malaysia. However, if OPF is to be utilized as a main fuel for industrial-scale firing/gasification plant, interruption in fuel supply may occur due to numerous reasons, for instance inefficient fuel processing and ineffective transportation. A secondary supporting solid fuel is therefore necessary as a partial component to the main fuel in such cases, where the secondary fuel is combusted with the main fuel to adhere to main fuel shortage. Gasification of two fuels together, known as co-gasification, is practiced worldwide, some in industrial scale. However, current practice utilizes biomass fuel as the secondary fuel to coal in co-gasification. This investigation explores into the feasibility of co-gasifying two biomass fuels together to produce syngas. OPF was chosen as the primary fuel and a selection of Malaysian biomasses were studied to discover their compatibility with OPF in co-gasification. Biomass selection was made using score-and-rank method and their selection criteria are concisely discussed. Â© 2014 Owned by the authors, published by EDP Sciences.